Energy recovery from landing aircraft - Zulkifli, Shamsul Aizam (2012)
Currently, renewable energy sources are the main driver for future electricity generation. This trend is growing faster in the developed countries in order to reduce the green house effect and also in response to the limited supply of oil, gas and coal which are currently the major sources for electric generation. For example, the main renewable energy sources are from wind energy and solar energy but these energies are only available to those countries that are exposed to these resources. In this thesis an alternative energy source is investigated where it can be generated from the moving objects or in form of kinetic energy. The idea is to convert the kinetic energy during landing aircraft into electrical energy which it can also be stored and transferred to the existing electrical network. To convert this kinetic energy to electrical energy, the linear generator (LG) and uncontrolled rectifier have been used for energy conversion. The LG have been modelled in 3-phase model or in dq model and combined with the diode rectitier that is used to generate the dc signal outputs. Due to the uncontrolled rectitier the electrical outputs will have decaying amplitude along the landing time. This condition also happen to the LG outputs such as the force and the power output. In order to control these outputs the cascaded buck-boost converter has been used. This converter is responsible to control the output current at the rectitier and also the LG output power during landing to more controllable power output. Here, the H1 current control strategy has been used as it offers a very good performance for current tracking and to increase the robustness of the controller. During landing huge power is produced at the beginning and when the landing time is increased, the generated input power from LG is reduced to zero. Due to this, the energy storage that consits of ultracapacitor, bidirectional converter and boost converter are usedin order to store and to release the energy depends on the input power source and load grid power. The voltage proportional-integral (PI) control strategy has been used for both the converters. The last part is to transfer the energy from the source and at the ultracapacitor to the load by using the inverter as the processing device. The power controller and current controller are used at the inverter in order to control the power flow between the inverter and the grid. This is when the reference power is determined from the load power in order to generate the reference current by using the voltage oriented controller (VOC), while the H1 current controller is used to regulate the inverter current in order to inject the suitable amount of current that refer to the load power. Finally, a complete energy recovery system for landing aircraft with the grid connection have been put together to make the whole system to be as a new renewable energy source for the future electricity generation.